2015
DOI: 10.3345/kjp.2015.58.3.102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human parechovirus and enterovirus in cerebrospinal fluid samples in children in Jinju, Korea

Abstract: PurposeHuman parechovirus (HPeV) and enterovirus (EV) are causative agents of a sepsis-like illness in neonates and of infections of the central nervous system in young children. The objectives of this study were to assess the prevalence of HPeV3 and EV infection in young children with a sepsis-like illness or with meningitis in Jinju, Korea.MethodsCerebrospinal fluid (CSF) samples were collected from 267 patients (age range, 1 day to 5 years) and assessed for HPeV and EV by performing reverse transcription po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…In a study of viral meningitis in Korea, it was found that individuals with enterovirus infections showed a protein concentration with a median value of 39 mg/dL and glucose of 59 mg/dL 19 , which is similar to this study findings.…”
Section: Discussionsupporting
confidence: 89%
“…In a study of viral meningitis in Korea, it was found that individuals with enterovirus infections showed a protein concentration with a median value of 39 mg/dL and glucose of 59 mg/dL 19 , which is similar to this study findings.…”
Section: Discussionsupporting
confidence: 89%
“…Recent data from the USA indicate that the peak season for HPeV detection was in the summer months [ 12 ]. The highly variable epidemiology of HPeV is supported by recent findings from South Korea, where the majority of cases were detected in spring in one study and in summer in another study [ 14 , 15 ]. However, both studies covered only a short period of time.…”
Section: Discussionmentioning
confidence: 52%
“…The costs of sensitive multiplex PCR assays continue to decline and results can be obtained within hours of receiving the sample in most diagnostic laboratories (68,81,82). It should be emphasised that there are multiple data which highlight that HPeV is routinely detected in CSF in the absence of pleocytosis (8,13,30,69,(83)(84)(85). CSF samples should therefore be routinely tested for HPeV in infants aged under 6 months (where the clinical burden is highest) during an acute illness irrespective of CSF white cell count.…”
Section: Improving Diagnosis Of Parechovirus Infectionsmentioning
confidence: 99%